Caregiver Burden is Associated with Cognitive Decline and Physical Disability of Elderly Post-Stroke Patients - Othman, Zahiruddin; Siong, Teck Wong; Drahman, Ismail; Zakaria, Rahimah (International Digital Organization for Scientific Information (IDOSI), 2014)
Caregiver burden following stroke is increasingly recognised as a significant health care concern. The present study found the prevalence of elderly patient’s post-stroke depression, cognitive impairment and caregiver’s burden to be 32%, 57.6% and 25%, respectively. Caregiver burden was significant, albeit weakly, correlated with cognitive decline (r=0.362, P 0.001) and physical disability (r=0.316, P=0.002) of elderly post-stroke patients. Otherwise, none of the socio-demographic characteristics of caregiver or patient, including depression, were significantly correlated with caregiver burden. This study highlighted the importance of regular assessment of cognitive function and physical disability of elderly post-stroke patients for early detection of caregiver burden, in addition to assessment of caregiver psychological wellbeing.